MAKNA SIMBOLIS ORNAMEN PINTU BLEDEG MASJID AGUNG DEMAK - Marsidik (BBPPMPV Seni dan Budaya Yogyakarta, 2023)
The current study aims to describe the symbolical meaning in the ornaments of “Bledeg” Doorof Demak Great Mosque viewed from three aspects, namely contour, content, and context. Theresults of the study demonstrate that analysed from the aspect of contour, ornaments of“Bledeg” Door consist of several parts, namely the crown, dragon head, and vase. There areseveral motifs originating from Majapahit, namely the “tumpal” motif and the use of SuryaMajapahit symbol stylized as dragon's eyes. The colors used are red, green, and white. Interms of content, the tumpal motif is a symbol of relationship of human beings with God, thecrown motif is a symbol of virtue, the dragon head motif is a symbol of strength in spreadinggoodness, the vase motif is a symbol of religion, and the floral plant motif is a symbol offertility, while the red, blue, and white colors symbolize safety. Viewed from the context, themyth of Ki Ageng Selo when catching lightning comes to light which is visualized into asymbolic ornament. The ornaments of “Bledeg” Door of Demak Great Mosque symbolizes therelationship between human beings and God signifying their privilege to spread God'steachings.